2021
DOI: 10.1177/18344909211039893
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy beliefs and attitudes toward COVID-19 vaccinations

Abstract: During the coronavirus pandemic, this study aimed to investigate the impact of conspiracy beliefs on Finnish attitudes toward vaccinations in general and COVID-19 vaccinations in particular. This study was a conceptual replication in Finland of a study by Pivetti et al. (2021) . Some 529 Finnish participants responded to a self-report questionnaire during the partial lockdown in Finland in spring 2020. The hypothesized relationships between variables of interest were integrated in a serial multiple mediation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 92 publications
(135 reference statements)
4
26
0
1
Order By: Relevance
“…Perceived risk was assessed with three questions taken from Dryhurst et al [12]: "How likely do you think it is that you will be directly and personally affected by the following in the next 6 months?-Catching the coronavirus/COVID-19", "How likely do you think it is that your friends and family in the country you are currently living in will be directly affected by the following in the next 6 months?-Catching the coronavirus/COVID-19", and "How much do you agree or disagree with the following statements?-Getting sick with the coronavirus/COVID-19 can be serious". For the first two questions, participants responded on a seven-point Likert scale, ranging from "not at all likely" (1) to "very likely" (7). For the third question, participants responded on a five-point Likert scale, ranging from "strongly disagree" (1) to "strongly agree" (5).…”
Section: Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived risk was assessed with three questions taken from Dryhurst et al [12]: "How likely do you think it is that you will be directly and personally affected by the following in the next 6 months?-Catching the coronavirus/COVID-19", "How likely do you think it is that your friends and family in the country you are currently living in will be directly affected by the following in the next 6 months?-Catching the coronavirus/COVID-19", and "How much do you agree or disagree with the following statements?-Getting sick with the coronavirus/COVID-19 can be serious". For the first two questions, participants responded on a seven-point Likert scale, ranging from "not at all likely" (1) to "very likely" (7). For the third question, participants responded on a five-point Likert scale, ranging from "strongly disagree" (1) to "strongly agree" (5).…”
Section: Perceived Riskmentioning
confidence: 99%
“…Generally speaking, Italy has a long-standing tradition of high coverage of vaccinations. However, in the last decade, the frequency of infant immunization has decreased alarmingly, leading to the introduction of a new law, the "Italian National Immunization Prevention Plan 2017-19" (n. 119/2017), which prescribes mandatory vaccinations against ten diseases for preschool and school-aged children [7]. The implementation of the law contributed to an increased awareness of the importance of vaccination in the Italian population [8].…”
Section: Introductionmentioning
confidence: 99%
“…Those on the left tend to support expanded government and increased spending, whereas those on the right usually support smaller government and reduced spending [26]. This spectrum has been used in relevant research on morality and politics in both North American [27] and European contexts [28], providing a meaningful way of pooling and comparing data from different nations. In turn, there is evidence of similar links between the left-right political spectrum and COVID-19 related attitudes and behaviours in U.S. and Canadian contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Further statistical analyses provided more arguments to establish validity, in particular convergent validity. The literature shows that endorsing vaccine conspiracy beliefs predicts general attitudes towards vaccine [56,57] . This relationship is verified in our study since our correlational analyses showed a positive correlation between total scores of the VAX scale and those of the Vaccine Conspiracy Beliefs Scale.…”
Section: Discussion and Limitationsmentioning
confidence: 99%